Hyperbaric oxygenation in peripheral ischaemic lesions in infants. Issue 4 (April 1985) - Rosenthal, E; Benderly, A; Monies-Chass, I; Fishman, J; Levy, J; Bialik, V
Abstract : Acute peripheral arterial occlusion may lead to gangrene, with loss of parts of arms and legs. Three infants with disseminated intravascular clotting developed dark red discoloration of the tips of fingers and toes which progressed proximally. Repeated hyperbaric oxygenation treatments caused regression of the demarcation line and further progression of necrosis stopped.